(untitled) - The World Bank (Washington, 2006)
TradeCAN 2005 is a comprehensive database and versatile toolbox for the analysis of the competitiveness of nations. It is based on the official UN international trade statistics, using the 4-digit standard international trade classification. It covers the period 1985-2002 for all exporter countries and incorporates 90% of world trade. Around the central concept of "market share," TradeCAN offers novel indicators of the quality, structure, and performance of international trade specialization of nations. TradeCAN 2005 contains a user-friendly interface that allows rapid data retrieval and easy report preparation. The "Exercises Guide" provides essential information regarding origin and coverage of the dataset, formulas, and more. The set of exercises is designed so the reader becomes familiar with the system by using it and it guides users step by step through the query and report options. This product will be highly useful to policy makers, consultants, academic researchers and students of international trade, providing empirical and analytical support for analyzing general and specific trade trends and comparative performance by countries and regions.
Keywords: Developing countries,Economics,World bank